Blind spots : when medicine gets it wrong, and what it means for our health - Makary, Marty (Bloomsbury Publishing, 2024)
When modern medicine issues recommendations based on good scientific studies, it shines. Conversely, when modern medicine is interpreted through the harsh lens of opinion and edict, it can mold beliefs that harm patients and stunt research for decades. In Blind Spots, Dr. Makary explores the latest research on critical topics ranging from the microbiome to childbirth to nutrition and longevity and more, revealing the biggest blind spots of modern medicine and tackling the most urgent yet unsung issues in our $4.5 trillion health care ecosystem. The path to medical mishaps can be absurd, entertaining, and jaw-dropping--but the truth is essential to our health.